Fundamentalisme dan Masa Depan Ideologi Politik Islam - Abdul Chalik (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2014)
This article elaborates the phenomenon of fundamentalism and the future of Islamic political ideology. Islamic ideology represents religious views, ideas and movements which aspire to bring Islam into practice in state and societal affairs. One variant of Islamic ideologies is fundamentalism which endeavors to return religious practices back to the pristine Islam based on the Qur??n and al-Had?th. Fundamentalism rejects all modes of understand-ding which are not based on the Qur??n and al-Had?th, and refuses secular methodology in interpreting the Qur??n. This type of Islamic ideology found its momentum when Saudi Arabia regime officially adopted Wahhabism, and when Egyptian intellectuals were united to fight against modernity. Both Saudi Arabia and Egypt became seeding ground for fundamentalism. Some young muslim scholars who studied there became agents for the dissemination dan transmission of the fundamentalist ideology throughout the world. In Indonesia, this ideology have developed since independence and the drafting of the constitution. In the Indonesian context, resistence from traditionalist and nationalit groups were so strong that enable to dam up the spread of fundamentalis ideas. However, fundamentalist ideology remains an important challenge for the future of Indonesian Islam.